Geochemistry and petrogenesis of mafic and intermediate dyke swarms in eastern Tafresh (Urumieh-Dokhtar magmatic belt) - Ahmadreza Ahmadi; Behnaz Hosseini (پترولوژی)
IntroductionThe Urumieh-Dokhtar magmatic belt is one of the most active magmatic regions of Iran during the Cenozoic era. There are differing views regarding the tectonomagmatic setting of this magmatism; some attribute it to active continental margin magmatism, island arcs, post-collisional regions, and intra-continental rifts (Hassanzadeh, 1993; Shahabpour, 2007; Ghasemi and Talbot, 2006). The study area as the other sections of the Urumieh-Dokhtar Belt, is the area of Eocene magmatic activity. The geochemical characteristics of volcanic rocks in the northeast of Tafresh are similar to those of magmatism in active continental margin subduction zones (Nasiri Bezanjani, 2006). In the eastern part of Tafresh, numerous dikes cut through Paleozoic and older sedimentary and volcanic units. K-Ar dating of these dikes indicates an age of 15.4 million years (Ghorbani et al., 2014). Babazadeh et al. (2022) have provided a U-Pb age of 17.5 million years for the mafic dykes. This study examines the petrology and geochemistry of the Mafic and intermediate dyke bodies located in the eastern part of Tafresh and discusses their tectonomagmatic setting.GeologyThe study area lies in the central part of the Urumieh-Dokhtar magmatic belt. Cenozoic sedimentary-volcanic deposits unconformably overlie Upper Cretaceous marly limestones due to the Laramide orogeny, which uplifted the region. Eocene units comprise   alternating marine and continental deposits of volcanic flows, pyroclastics, and sediments.Marine transgression during early Eocene introduced marl-sandstone units (E1), followed by dominant volcanic activities forming basaltic to rhyolitic flows and pyroclastics (E2). Continental red deposits and marine green layers alternate. Later, marine conditions resumed (E3), forming sedimentary layers with green tuffs, while subsequent continental volcanic phases (E4) produced dacitic flows and tuffs. Renewed marine sedimentation (E5) followed, then thick terrestrial volcanic layers of andesitic-basalts (E6).Extensive dykes, mostly basaltic-intermediate, intrude older units, with U-Pb dating indicating Miocene age (17.5 Ma).Analytical method8 samples with the least alteration were selected for analysis of major and trace elements. The analysis of major and trace elements was carried out using the ICP-MS method (LF200 analytical system) at the ACME-Bureau Veritas Laboratory in Canada. For the study of the chemistry of clinopyroxene, plagioclase, and amphibole minerals, 15 points were analyzed using an electron microprobe at the University of Milan, Italy.Petrography and mineral chemistryDiabase: These rocks display a doleritic texture with minimal groundmass. Plagioclase crystals dominate (70 vol.%). The other primary minerals include clinopyroxene and iron-titanium oxides, while amphibole, alkali feldspar, olivine, and apatite appear as accessory minerals. Secondary minerals, such as calcite, chlorite, and epidote, form from plagioclase and clinopyroxene alteration.Basaltic andesite: These rocks comprise plagioclase (60–70 vol.%), amphibole (10–20 vol.%), iron-titanium oxides (5–10 vol.%), and clinopyroxene (5–10 vol.%), with accessory alkali feldspar, olivine, and apatite. Phenocrysts make up to 40 vol.% of the total volume, primarily plagioclase and amphibole. Secondary minerals, including chlorite and epidote, are present in the groundmass.Andesite: The primary minerals in these rocks are plagioclase (70–80 vol.%), iron-titanium oxides (10–20 vol.%), and amphibole (5–10 vol.%), with minor pyroxene, alkali feldspar, and apatite in the groundmass. The matrix consists of plagioclase microlites and fine-grained oxides, with secondary minerals like calcite, epidote, and sericite.The clinopyroxene crystals are of the salite type, and the plagioclase crystals ranging in composition from labradorite to andesine. Additionally, the amphiboles are of the pargasite type.GeochemistryThe continuity of trends in Harker diagrams for the studied samples suggests a common origin. Increasing Na2O+K2O and decreasing MgO, FeOt, TiO2, Al2O3, and CaO/Na2O along with increasing SiO2 indicate that the crystallization and separation of ferromagnesian minerals (especially clinopyroxene) with feldspar and Fe-Ti oxides played a significant role in the magmatic evolution of these rocks.On TAS diagram, the samples are classified as basalt, basaltic andesite, and andesite. Using immobile elements on the Zr/TiO2 versus Nb/Y diagram, the samples fall within the basaltic andesite field. All samples plot in the sub-alkaline field on the alkaline-subalkaline discrimination line. On AFM diagram, the samples lie near the boundary between tholeiitic and calc-alkaline series. Based on K2O versus SiO2, they range from medium-K calc-alkaline to low-K tholeiitic compositions.The chondrite-normalized REE patterns show enrichment in LREE relative to MREE and HREE, with flat MREE-HREE trends. The spider diagram normalized to the primitive mantle reveals LILE enrichment and HFSE depletion.Source and Tectonomagmatic SettingThe gentle slope between HREEs and MREEs in the REE pattern is consistent with the magma's origin from a spinel lherzolite mantle with little or no garnet involvement. Furthermore, in the Dy/Yb versus La/Yb diagram, the studied rocks fall within the range of melts originating from a spinel lherzolite mantle, and in the Nb/La versus La/Yb diagram, they lie within the lithospheric mantle field.Based on Nb/Th ratio versus Nb and the Ba/Nb ratio versus La/Nb, the studied rocks are located in the volcanic arc-related rocks field. In the Th-Hf-Ta diagram, the samples are placed within the magmatic arc-related rocks field. Also, based on the Nb/La ratio versus La/Yb, the samples fall within the active continental margin-related rocks field. However, in the Th/Yb versus Ta/Yb diagram, the samples fall within both the island arc and active continental margin-related rocks fields. Overall, the studied rocks display some characteristics to those of Island arcs and some others to those of active continental margins.ConclusionThe rare earth element patterns indicate that the magma associated with these igneous rocks originated from partial melting of the shallow lithospheric mantle in the spinel peridotite facies, with minimal or absent garnet involvement. Additionally, the observed characteristics in the incompatible element patterns, such as enrichment of mobile elements over rare earth elements and depletion of immobile elements, along with analyses in various geochemical diagrams, suggest their association with subduction-related magmatism. However, the studied rocks display geochemical criteria belonging to island arc as well as active continental margin magmatismThe intermediate geochemical features of island arc and active continental margin magmatism, along with other evidence including the association of these igneous rocks with a thick sequence of green tuffs and other shallow marine sediments indicate that the rocks under study originated in an intra-continental back-arc basin